DEVELOPING TOURISM POTENTIAL ON FORMER MINING LANDS BASED ON SUSTAINABLE DEVELOPMENT COMMUNICATION (STUDY IN SELINGSING RECLAMATION VILLAGE, EAST BELITUNG) - Iswanto, Doni; Yang Gusti Feriyanti (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The development of tourism on former mining land through sustainable development communication strategies is the subject of this study. The study focuses on Kampung Reklamasi Selingsing in East Belitung, where the local BUMDes works to attract both local and foreign tourists by utilizing the potential of the reclaimed land, such as the panorama. The study uses qualitative methods, including observation and interviews with BUMDes and PT Timah Tbk. The results show that BUMDes Selinsing has made various efforts to develop Kampung Reklamasi Selingsing as a tourist destination, including working with PT Timah to manage and develop the area with the concept of agro-edu tourism. Additionally, BUMDes Selinsing has improved the quality of facilities and services in the tourist area and is involved in the management of the Kampung Reklamasi Selingsing tourist area. The sustainable development communication strategy in the development of tourism in Kampung Selinsing involves collaboration with private parties, government agencies, and non-governmental organizations to obtain greater support and investment. The management of the area is sustainable, and the income from the tourism sector is used for sustainable development and the development of a more attractive area.